2024
DOI: 10.1002/admt.202301697
|View full text |Cite
|
Sign up to set email alerts
|

Microfluidic Droplet‐Based Tailorable Porous GelMA Microspheres for 3D Spatio Controllable Cell Coculture

Yaolei Wang,
Ting Du,
Xin Hao
et al.

Abstract: For the construction of accurate 3D tissue models in vitro, the 3D coculture model formed by spatio‐controlled distribution of multiple cells is essential. Despite the benefits of porous microspheres with low density, large surface area, and high permeability, exact spatio‐controlled distribution fails to appear in 3D coculture models by using porous microspheres as carriers. Herein, a facile method is proposed to construct a 3D coculture model with heterogeneous cell spatio‐tailored distribution using GelMA m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 52 publications
0
0
0
Order By: Relevance
“…18,20 Compared to other materials such as GelMA and PuraMatrix, alginate exhibits the unique characteristics such as natural origin, mild gel formation condition, and versatile modifiability. 21,22 In our group's previous research, we found that by dissolving Alg in Dex solutions, porous Alg microspheres that directly encapsulate the cells were formed in the PEG-CaCl 2 collection solution by using the dripping method. 18 Based on the above reasons, we hypothesized that multicompartmental gel microcarriers could be prepared by controlling the fusion of Dex-Alg droplets in the doublelayered collection solutions comprising an upper PEG solution and a lower Dex-CaCl 2 solution.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…18,20 Compared to other materials such as GelMA and PuraMatrix, alginate exhibits the unique characteristics such as natural origin, mild gel formation condition, and versatile modifiability. 21,22 In our group's previous research, we found that by dissolving Alg in Dex solutions, porous Alg microspheres that directly encapsulate the cells were formed in the PEG-CaCl 2 collection solution by using the dripping method. 18 Based on the above reasons, we hypothesized that multicompartmental gel microcarriers could be prepared by controlling the fusion of Dex-Alg droplets in the doublelayered collection solutions comprising an upper PEG solution and a lower Dex-CaCl 2 solution.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, the disposal of waste oil poses environmental concerns and requires professional treatment before discharge, thereby raising costs. An aqueous two-phase system (ATPS) referred to a two-phase system formed by mixing two incompatible aqueous solutions, typically with polymers, salts, or other additives dissolved in water, where under specific conditions water separated into two distinct phases. Due to the extremely high biocompatibility of the two aqueous phases, it had been proven to be used in cell culture studies in vitro. , Alginate (Alg) serves as a commonly used 3D coculture material with many advantages in cell culture and tissue engineering fields. , Compared to other materials such as GelMA and PuraMatrix, alginate exhibits the unique characteristics such as natural origin, mild gel formation condition, and versatile modifiability. , In our group’s previous research, we found that by dissolving Alg in Dex solutions, porous Alg microspheres that directly encapsulate the cells were formed in the PEG-CaCl 2 collection solution by using the dripping method . Based on the above reasons, we hypothesized that multicompartmental gel microcarriers could be prepared by controlling the fusion of Dex-Alg droplets in the double-layered collection solutions comprising an upper PEG solution and a lower Dex-CaCl 2 solution.…”
Section: Introductionmentioning
confidence: 99%